Development of novel 3D scaffolds using BioExtruder by the incorporation of silica into polycaprolactone matrix for bone tissue engineering. (December 2019) - Pattanashetti, Nandini A.; Biscaia, Sara; Moura, Carla; Mitchell, Geoffrey R.; Kariduraganavar, Mahadevappa Y.
Graphical abstract: Highlights: Development of 3D printed scaffolds by novel fused deposition modelling technique -BioExtruder. Effect of SiO2 incorporation on PCL scaffolds was studied by varying the content of SiO2 from 5 wt% to 15 wt%. Developed 3D scaffolds possessed high interconnected porous structure with enhanced hydrophilicity. Scaffolds demonstrated enhanced mechanical strength and cell proliferation with increased SiO2 content and thus a potential candidate for bone tissue engineering. Abstract: Development of three-dimensional (3D) scaffolds has acquired a great importance for bone repair and tissue reconstruction. Thus, this paper addresses the development of 3D scaffolds by varying the content of silicon dioxide (SiO2 ) in polycaprolactone (PCL) matrix. The scaffolds were fabricated by employing a novel fused deposition modelling technique (BioExtruder). The physicochemical properties of the developed 3D scaffolds were systematically studied using various techniques. The thermal properties and stability of the PCL and its composites were assessed using differential scanning calorimetry and thermogravimetric analysis. The morphology of the developed scaffolds was evaluated using scanning electron microscopy and optical microscopy, and found that the pore size was increased from 270 to 320 μm with increasing the SiO2 content in the PCL matrix. The wettability of the developed scaffolds was assessed using contact angle meter. The scaffold incorporating 15 wt% of SiO2 exhibited the highest hydrophilic property as well as thermal stability. The Young's modulus value determined using universal testing machine indicated that the scaffold developed with 15 wt% of SiO2 exhibits 101.59 MPa. To assess the performance of the scaffolds for tissue engineering applications, the in-vitro cytotoxicity and cell proliferation were systematically carried out using L929 Mouse Fibroblasts and MG63 Osteoblasts, respectively. It was found that the scaffolds did not show any toxic effects towards the cell growth, and the cell proliferation was greatly increased >90% during 7 days of cell culture. Based on the results, it is concluded that the scaffold containing 15 wt% of SiO2 is of potential candidate for bone tissue engineering application.